Encyclopedia of Membranes - Drioli, Enrico; Giorno, Lidietta (Springer Berlin Heidelberg : Imprint: Springer, 2016)
A landmark work covering the major aspects of the science, technology and application of membrane operations and related fields, from basic phenomena to the most advanced applications and future perspectives. Over 1500 concise entries in an A-Z format cover a vibrant field with a multitude of applications in diverse disciplines such as biotechnology, medicine, agro-food and petrochemical industries, environmental protection, as well as drinking water supply. Coverage includes membrane reactors and catalytic design (catalytic membrane reactors). Practically all unit operations of process engineering can be redesigned as membrane unit operations (e. g. membrane distillation, membrane crystallization, membrane stripping, membrane scrubbing). Entries are provided by an international team of experts from academia, research institutions as well as from industry.